Blockchain Technology and Its Application - Burygin I. E. (A breakthrough in science: development strategies, 2020)
the article discusses the basic principles of the operation of Blockchain technology, its advantages and disadvantages. Particular attention is paid to the role of Blockchain in the development of a digital society. Various areas of application of this technology and features of use are shown.
Keywords: информационное общество; криптовалюта; information society; mining; cryptocurrency; цифровая экономика; блокчейн; хэширование; смарт-контракты; digital economy; майнинг; финансовая технология; blockchain; financial technology; smart contracts; layered hashing